Exposure of students (pupils) and employees of educational institutions in the Leningrad region to natural sources of radiation. Part 1: Results of a comprehensive survey - A. S. Vasilyev (Радиационная гигиена)
Currently, there is no methodological support for radiation monitoring and sanitary and epidemiological assessment of radon concentration (or radon EEC) and other parameters of the radiation situation in existing operated buildings. The paper presents a review of the protocols for conducting measurements of indoor Leningrad region with previously found elevated levels of radon concentration using long-term measurements. The survey revealed that highest values of indoor radon ECC were obtained using instant measurements in several educational institutions both in the normal operation mode of the buildings (up to 1106 Bq/m3) and after leaving the premises for 12 hours with closed windows and doors (up to 1586 Bq/m3) according to the requirements of paragraph 6.5 of MU 2.6.1.2838-11. High values of radon concentration were also obtained using long-term and short-term measurements (up to 4900 and 1420 Bq/m3, respectively). In addition, high values of radon flux density were detected (up to 2030 mBq/(m2·s)). The established hygienic norms for ambient dose equivalent rate indoors and outdoors were not exceeded in the surveyed educational institutions. The levels of gross alphaand beta activities in tap water sampled from the surveyed educational institutions were below the control levels, and an exceedance of intervention level for activity concentration of radon in analyzed samples was not detected. The results of the survey will be used for hygienic assessment of doses and health risks for students (pupils) and employees of several educational institutions of the Leningrad region due to exposure to radon and its progeny and can be used to improve the method for indoor radon concentration monitoring in existing operated public buildings in the Russian Federation, which in turn will make it possible to obtain correct values of public doses and health risks.